Geoinformation metadata in INSPIRE and SDI understanding. editing, publishing - Litwin, Leszek (Lecture Notes in Geoinformation and Cartography, 2011)
The book is a new comprehensive textbook about creating and publishing geoinformation metadata. It is a compendium of knowledge about geoinformation metadata in INSPIRE Directive and Spatial Information Infrastructures. It contains the knowledge necessary to understand prior to the creation of geoinformation metadata. Metadata data about data - describe the layers of spatial data (data series, services) responding to the questions: what, why, when, who, how and where Geoinformation metadata allows for exact search of the spatial data according to given criteria, regardless of where this data is located. On 15 May 2007 the EU Directive 2007/2/EC came into force establishing Infrastructure for Spatial Information in Europe - INSPIRE. The proper functioning of the infrastructure for spatial information would not be possible without the metadata.